Odpowiedzi

2010-02-16T17:45:32+01:00
A) (-1 1/2) : (- 0,06) = (-1,5):(-0,06) = 25
b) (-2 2/3) : 1,2 = (-8/3):(6/5) = (-8/3)*(5/6) = -20/9
c) 2/3 : (-6) = 2/3*(-1/6) = -1/9
d) (-0,45):1 4/5 = (-0,45):(1,8) = -0,25
e) (-2,75):(2,2) = -1,25
f) (-3,5):(-1 2/5) = (-3,5):(-1,4) = 2,5
2010-02-16T17:49:39+01:00
A) (-1 1/2) : (- 0,06) =(-1,5):(-0,06)=25
b) (-2 2/3) : 1,2 =-2 2/9
c) 2/3 : (-6) =-2/18=-1/9
d) (-0,45):1 4/5=-0,25
e) (-2,75):(2,2)=-1,25
f) (-3,5):(-1 2/5)=2,5
mam nadzieje że pomogłam
2010-02-16T17:52:36+01:00
A)(-1 1/2);(-0.06)=-1.5: (-0.06)= 25
b)(-2 2/3): 1.2= -2 2/3 :10/2= -8/3 * 2/10=8/15
c)2/3:(-6)= 2/3*(-1/6)= -1/9
d)(-0,45):1 4/5=-0.45 : 1,8= -0,25
e)(-2,75):(-2,2)= 1,25
f)(-3,5):(-1 2/5)= -3,5:(-1,4)= 2,5